Occupational stress and body composition of hospital workers: a follow-up study - de Lira, Carlos Rodrigo Nascimento; Akutsu, Rita de Cássia Coelho de Almeida; Coelho, Lorene Gonçalves; Zandonadi, Renata Puppin; Costa, Priscila Ribas de Farias (Frontiers in Public Health, 2024)
This study sought to analyze the influence of occupational stress on the body composition of hospital workers after one year of follow-up. This prospective cohort study included 218 workers from one of the leading private hospitals in the municipality of Santo Antônio de Jesus, Recôncavo da Bahia region, Northeast Brazil. Body composition was analyzed by proxy (Body Mass Index and Waist Circumference) and Bioelectrical Impedance Analysis. The primary exposure adopted in the present study was the perception of occupational stress, assessed with the adapted and reduced version of the Job Content Questionnaire evaluating demand and control dimensions. The covariates were work characteristics; biological characteristics; sociodemographic characteristics and lifestyle. Statistical analyses were performed using descriptive, bivariate and multivariate analysis. At the first stage of the study, we identified that 55.96% (n=122) of workers had high work demand and 25.22% (n=55) had low control. Among those who had high demand and low control at the beginning of the study, the majority were women, non-white, with low educational and income levels, sleeping less than 7 hours/day. After 12 months of follow-up, the median value for demand continued as 13 (IQR: 5 -25) and for control, it increased to 16 (IQR: 9 -23). In this second moment of the study, 62.38% (n=136) of workers showed high demand and 45.87% (n=100) low control. The characteristics of workers with high demand and low control were similar to those of the first moment. The results indicate that high demand and low control at work are risk factors for changes in body mass index, fat mass and fat-free mass in hospital workers. This study shows the importance and need for clinical and epidemiological assessments regarding the body composition of professionals working in hospitals, since high rates of overweight and obesity are triggers of chronic health problems such as dyslipidemia, diabetes mellitus and cardiovascular diseases, among others. Therefore, managers must promote adequate working conditions and understand the need for periodic body composition assessments.